Measurement of D*±, D± and Ds ± meson production cross sections in pp collisions at sv=7 TeV with the ATLAS detector; Nuclear Physics B; Vol. 907 - Aad G.; Abbott B.; Abdallah J.; Abdinov O.; Klimentov A. A. Aleksey Anatoljevich (2016, 2016)
Title screen